Monitoring Investments - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
This note provides guidance on how to monitor the performance and impact of agricultural investments, and on which aspects to observe. Ongoing monitoring of investments is a key way to hold investors accountable for contractual commitments and deliver the expected benefits to the country and surrounding communities. It also facilitates early identification of emerging negative impacts or of failing investments, enabling remedial actions. Monitoring is often deficient because of a lack of resources and systematic procedures, which allows negative impacts to escalate beyond what will otherwise be the case. Internal monitoring is likewise good practice for investors and their financiers, though the field research indicated room for improvement.